2016
DOI: 10.1182/asheducation.v2016.1.24.088333
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-related myeloid neoplasms: does knowing the origin help to guide treatment?

Abstract: Therapy-related myeloid neoplasms (t-MN) combine t-MDS and therapy related acute myeloid leukemia (t-AML) patients in one entity because of their similar pathogenesis, rapid progression from t-MDS to t-AML, and their equally poor prognosis. Treatment with epipodophyllotoxins like etoposide has been associated with a short interval between treatment and development of t-AML, with fusion oncogenes like KMT2A/MLL-MLLT3 and a better prognosis. In contrast, treatment with alkylating agents has been associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…The ICD codes used by the Swedish Cancer Registry do not specify treatment-related cancers, although the literature suggests that treatment-related cancers now account for 7% of acute myeloid leukaemia. 19 The study periods were constrained by the availability of data.…”
Section: Implications Of All Available Evidencementioning
confidence: 99%
“…The ICD codes used by the Swedish Cancer Registry do not specify treatment-related cancers, although the literature suggests that treatment-related cancers now account for 7% of acute myeloid leukaemia. 19 The study periods were constrained by the availability of data.…”
Section: Implications Of All Available Evidencementioning
confidence: 99%
“… 5 , 7 It has been suggested that malignant cells with multiple aberrations are more immunogenic than cells with one or a few aberrations, and thus novel immune-based therapies, such as chimeric antigen-receptor T cells, bi-specific antibodies, and checkpoint inhibitors, should be considered in t-MN with a highrisk genetic profile and their evaluation in clinical trials should be encouraged. 4 Cytogenetic classification of t-AML should be further evaluated as a potential prognostic marker, and treatment recommendations should be based on performance status and karyotype. Recent unbiased approaches driven by gene expression analysis and Next Generation Sequencing have contributed to the identification of unique biomarkers associated with leukemia, which have the potential to significantly improve the diagnostic and prognostic criteria, and contribute to the continuous adaptation of treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, t-MN should be distinguished from AML with myelodysplasia (secondary AML), which is diagnosed either when 50% or more of the bone marrow cells are dysplastic in at least two lineages, when the patient had a previous diagnosis of MDS or MDS/MN or when myelodysplasia-associated cytogenetic aberrations are present. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…However, MMR does not remove the methylated base, and becomes a permanent mutation. This results in DSBs, leading to resistance to killing by methylating agents [ 7 , 17 , 21 , 23 ].…”
Section: Etiology Of Therapy-related Myeloid Neoplasmsmentioning
confidence: 99%
“…These inhibitors interfere with the re-ligation step during DNA replication and generate single-stranded DNA for the cancer cells. This mechanism reduces the progression and proliferation of cancer cells [ 17 , 19 ]. However, these inhibitors are not specific for cancer cells, and also cause DSBs of the normal cell DNA.…”
Section: Pathogenesis Of Therapy-related Myeloid Neoplasmmentioning
confidence: 99%